BUILD STUDENTS’ CHARACTER THROUGH FASTING AT MUSLIM SCHOOL - Dermawan, Oki (Pascasarjana IAIN Kudus, 2017)
Spiritual intelligence is Supposed to be the main concern in education. This is done by the teaching of religious ethical values by example from the family, school and community. through the practice of worship, Such as fasting a month in Ramadhan (Refrain from eating and drinking or anything that may nevertheless invalidate the fast, all day from dawn until sunset in the month of Ramadan). fasting, reading and understanding the holy book the Qur'an, physical and social environment conducive. when the spirituality of the students are organized, it will be Easier to organize other aspects of personality. Fasting during Ramadan is a momentum for character building. Fasting will let people have strong principles, patience, Sincerity and do not give up and have the solidarity and love each other. That principle has now started to disappear. Moment of Ramadan may also be a school agenda for character building, with this media, students are expected to remember and go back to the true identity of the sacred and sublime, with the values of humanity and wisdom. When the values of human nature come back on the track, then the equality and solidarity will color the days of the students. Fasting has a horizontal dimension with a strong social life Such as charity, served meals to the orphans, be patient in facing the problem. there are some excellent values for building the character of students. It is Appropriate if the moment of Ramadan fasting would be passed on in the schools as a program after the month of Ramadan in shaping the character of students through the activities of the sunnah fasting( not compulsory fasting) twice a week Monday-Thursday, or give students the freewill to negotiate to determine how many times a week or every month held sunnah fasting together, the idea of the Sunnah fasting is influence on the formation of student character effectively.